CONTRASTING GLACIAL/INTERGLACIAL REGIMES IN THE WESTERN ARCTIC OCEAN AS EXEMPLIFIED BY A SEDIMENTARY RECORD FROM THE MENDELEEV RIDGE - Polyak L.; Curry W.B.; Darby D.A.; Bischof J.; Cronin T.M. (My University, 2004)
Distinct cyclicity in lithology and microfaunal distribution in sediment cores from the Mendeleev Ridge in the western Arctic Ocean (water depths ca. 1.5 km) reflects contrasting glacial/interglacial sedimentary patterns. We conclude that during major glaciations extremely thick pack ice or ice shelves covered the western Arctic Ocean and its circulation was restricted in comparison with interglacial, modern-type conditions. Glacier collapse events are marked in sediment cores by increased contents of ice-rafted debris, notably by spikes of detrital carbonates and iron oxide grains from the Canadian Arctic Archipelago. Composition of foraminiferal calcite δ18O and δ13C also shows strong cyclicity indicating changes in freshwater balance and/or ventilation rates of the Arctic Ocean. Light stable isotopic spikes characterize deglacial events such as the last deglaciation at ca. 12 14C kyr BP. The prolonged period with low δ18O and δ13C values and elevated contents of iron oxide grains from the Canadian Archipelago in the lower part of the Mendeleev Ridge record is interpreted to signify the pooling of freshwater in the Amerasia Basin, possibly in relation to an extended glaciation in arctic North America. Unique benthic foraminiferal events provide a means for an independent stratigraphic correlation of sedimentary records from the Mendeleev Ridge and other mid-depth locations throughout the Arctic Ocean such as the Northwind and Lomonosov Ridges. This correlation demonstrates the disparity of existing age models and underscores the need to establish a definitive chronostratigraphy for Arctic Ocean sediments.
Keywords: Arctic Ocean; Quaternary; stratigraphy; paleoceanography; glaciation; ice rafting; Foraminifera; Ostracoda; stable isotopes; provenance; Cenozoic::Quaternary; Кайнозой::Четвертичная